DATA PROCESSING AND VISUALIZATION IN SOFTWARE DEFINED VEHICULAR NETWORK TESTBED - Afif, Farhan
The invention of the internet has revolutionized various fields, accelerating advancements across sectors. Instant and efficient information exchange has spurred progress in economics, social sciences, politics, geography, entertainment, and more. Additionally, advancements in computer networks and transportation mutually reinforce each other, notably with the introduction of Software-Defined Networking (SDN), a dynamic and centralized approach that separates control and data planes. Simultaneously, the transportation sector is undergoing a revolution with the implementation of automation and advanced sensors in vehicles. These developments have led to the creation of various supporting software in both fields, including Mininet and SUMO (Simulation of Urban Mobility). Mininet is a simulator for SDN networks, while SUMO simulates road traffic. Both are crucial for developing Intelligent Transportation Systems (ITS), but their integration for simulating Software-Defined Vehicular Networks (SDVN) remains unrealized. Mininet and SUMO are CLI-based (Command Line Interface), making them less user-friendly. Therefore, a user-friendly and integrated simulation for SDVN is needed. We developed an SDVN testbed that integrates Mininet and SUMO within a web application, providing various simulation scenarios and network protocols as parameters. The web app is desained for user-friendliness, ensuring high-quality and easily analyzable simulation data. The testbed automates Mininet and SUMO, requiring users to only input parameters and receive output. Users can configure parameters like topology, vehicle count, protocols, speed, and transmission power. The web app's output includes network output (e.g., RSSI, jitter, throughput) from Mininet and mobility output (e.g., fcd position, fcd speed) from SUMO. Raw simulation data is processed and visualized for easier analysis. With this SDVN testbed, we aim to support researchers in automated vehicles and ITS, and advance SDN by expanding its application in transportation. The testbed not only provides an accessible tool for researchers but also paves the way for further innovation in network and transportation technology integration. We believe that integrating Mininet and SUMO will significantly impact intelligent transportation technology development. It enables more realistic and